2015
DOI: 10.1016/j.healun.2014.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for invasive fungal disease in heart transplant recipients

Abstract: BACKGROUND Heart transplant (HT) recipients are at risk for invasive fungal disease (IFD), a morbid and potentially fatal complication. METHODS We performed a retrospective cohort study to evaluate the incidence and risk factors for IFD in HT recipients from 1995 to 2012 at a single center. IFD cases were classified as proven or probable IFD according to current consensus definitions of the European Organization for Research and Treatment of Cancer/Mycoses Study Group. We calculated IFD incidence rates and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 16 publications
1
44
2
1
Order By: Relevance
“…In 2011, the TRANSNET investigators reported a 12‐month cumulative incidence of 0.07% in SOT, compared with 0.29% in hematopoietic stem cell transplantation, across 23 institutions . In the two largest single‐center reviews of mucormycosis in SOT, invasive fungal infections occurred in 6%‐8% of patients post heart transplant, with the vast majority being Candida and Aspergillus . In the Stanford experience, only four cases of zygomycetes occurred among 108 fungal infections …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, the TRANSNET investigators reported a 12‐month cumulative incidence of 0.07% in SOT, compared with 0.29% in hematopoietic stem cell transplantation, across 23 institutions . In the two largest single‐center reviews of mucormycosis in SOT, invasive fungal infections occurred in 6%‐8% of patients post heart transplant, with the vast majority being Candida and Aspergillus . In the Stanford experience, only four cases of zygomycetes occurred among 108 fungal infections …”
Section: Discussionmentioning
confidence: 99%
“…Invasive fungal infections are reported to occur in 6%‐8% of patients post heart transplantation and are associated with significant morbidity and mortality . The majority of fungal infections following heart transplantation are caused by Candida and Aspergillus species .…”
Section: Introductionmentioning
confidence: 99%
“…21 A retrospective cohort study in heart transplant recipients found that utilisation of muromonab was associated with an increased risk of IFI (HR 2.68; 95% CI: 1.16-6.2), with IFIs being attributed mainly to Candida and secondarily, to Aspergillus. 22 In contrast, a randomised multicentre trial on adults with steroid-resistant acute GVHD revealed that muromonab use was correlated with a decreased (P=.059) incidence of IFIs as compared to high-dose steroids alone. 23 As regards to paediatric use (Table 1), a prospective, multicentre register study of children who underwent heart transplantation showed that patients who received induction had a lower risk for early fungal infections (HR 0.6; 91% CI: 0.40-0.91; P=.016).…”
Section: Anti-cd3 Monoclonal Antibodiesmentioning
confidence: 91%
“…In an uncontrolled study of infectious complications after muromonab induction in 122 adult liver transplant procedures, 19 IFIs (15.6%) were recorded, including 16 due to Candida spp, two cases of cryptococcosis and one case of aspergillosis . A retrospective cohort study in heart transplant recipients found that utilisation of muromonab was associated with an increased risk of IFI (HR 2.68; 95% CI: 1.16‐6.2), with IFIs being attributed mainly to Candida and secondarily, to Aspergillus . In contrast, a randomised multicentre trial on adults with steroid‐resistant acute GVHD revealed that muromonab use was correlated with a decreased ( P =.059) incidence of IFIs as compared to high‐dose steroids alone …”
Section: Inhibition Of T‐cell‐mediated Pathologymentioning
confidence: 99%
“…Ces différents agents fongiques sont susceptibles d'augmenter la mortalité et la morbidité des patients [8][9][10] ; (3) les traitements antibiotiques pourraient faciliter le développement des infections fongiques pulmonaires chez ces patients. De même, l'utilisation de traitements immunosuppresseurs (corticosté-roïdes au long cours ou autres) favorise le développement d'infections fongiques invasives et graves, en particulier dans un contexte de transplantation, mais éga-lement sur fond de pathologie chronique telle que la BPCO où des cas d'aspergillose semi-invasive ont été rapportés [11][12][13] ; (4) enfin, les champignons sont capables d'interagir notamment avec des bactéries [14]. Ils peuvent aussi former des biofilms et induire une résistance aux traitements anti-infectieux.…”
Section: (➜)unclassified